Sistem Tata Kelola Tagihan Pembayaran Klaim Jaminan Kecelakaan Kerja Pada BPJS Ketenagakerjaan Cabang Surabaya Karimunjawa - Melinda Wahyuning Putri; Nurul Azizah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
BPJS Employment cooperates with many employer companies and Work Accident Service Centers in managing Work Accident Insurance. In its management, of course, the company must have an effective and efficient governance system. The research entitled "Governance System for Payment Bills for Work Accident Guarantee Claims at Bpjs Ketenagakerjaan Surabaya Karimunjawa Branch" has the aim of conducting an ongoing analysis of the governance of bills for payment of work accident guarantee claims. The results obtained in this study are that researchers know the benefits of Work Accident Insurance and the procedures and Management System for JKK Payment Bills which are carried out very well by the BPJS Employment Surabaya Karimunjawa.